The Role of Students in Religious Development in Society: (Community service in Rancajawat Village, Tukdana District, Indramayu Regency) - Mubarok, Frenky (Kusuma: Jurnal Pengabdian kepada Masyarakat, 2024)
Community service activities by lecturers and students of IAI Pangeran Dharma Kusuma Segeran Indramayu were carried out in Rancajawat Village, Tukdana District, Indramayu Regency, for 43 days, starting from January 15 to February 26, 2024, as part of the Real Work Lecture (KKN) program. This activity focuses on religious development with the aim of increasing understanding, awareness, and practice of Islamic values ​​in the community. Various activities are carried out in strategic locations such as residents' homes, prayer rooms, mosques, schools, and KKN posts. Personal religious guidance is carried out in residents' homes, while activities in prayer rooms and mosques include training in reading the Qur'an, religious studies, lectures, and worship training. At school, students provide religious training aimed at forming Islamic character in students. The KKN post functions as a center for coordinating activities and discussions to design programs according to community needs. This program is expected to be able to strengthen Islamic values, strengthen relations between universities and the community, and create a sustainable positive impact on the social and spiritual lives of the residents of Rancajawat Village.